Formulation and charecterization of didanisine micro beads - Nansri saha (International Journal of Pharmacy and Analytical Research, 2025)
From past few years Microbeads have been studied by many workers as a choice of novel drug delivery system to provide a better drug bioavailability considering, high penetration property of the Microbeads encapsulated agents through biological membrane and the stability of them. The present formulation study on Didanosine is an attempt to prepare Microbeads drug delivery system and evaluate its performance. The formulations were prepared, varying the ratios of polymer and sodium alginate/ sodium bicarbonate, by emulsification and ionic gelation method. An ideal or best formulation of Microbeads is the one which gives high entrapment efficiency along with good stability and drug release profile. In the present study entrapment efficiency is found to be drug and polymer ratio dependent. The release rate is found to be depended on polymer concentration and addition of the cations like Calcium chloride.